Psycho-Social Aspects of Human Sexuality and Ethics - Sultan Sheriff, Dhastagir (IntechOpen, 2021)
With the emerging newer trends in sexuality and clashes with the traditional practice of human sexuality, there is a need for introspection and a framework of ethical principles that may guide human sexuality and its practice. Human sexuality is more than a biological phenomenon. Open discussions about sexual identity and sexual practices will help people better understand themselves, others, and the world around them. This book gives a panoramic view of certain aspects of human sexuality in health and disease.